Thomas Cole ve Sanatı - Çetin, Ufuk (Muş Alparslan Üniversitesi, 2021)
Thomas Cole is a British landscape painter born in 1801 in Lancashire Bolton, England and immigrated to the States with his family in 1818. He is the founder of America's first landscape painting school in the 19th century, known as the Hudson River School. The emergence of a national painting school showed people environmental awareness and landscape painting. His works emphasize rapid technological developments experienced in 19th century America and lost humanity moving away from its values. Besides his paintings, he wrote many works as a poet and author. He is a foreign painter reminding Americans caring wild beauty and art of painting they have as an Englishman.

Thomas Cole, 1801’de İngiltere Lancashire Bolton’da doğmuş ve 1818’de ailesiyle birlikte Amerika Birleşik Devletleri’ne göç etmiş İngiliz kökenli bir manzara ressamıdır. Hudson River School olarak bilinen Amerika’nın 19. yüzyıldaki ilk manzara resim okulunun kurucusudur. Milli bir resim okulunun ortaya çıkmasını da sağlayarak insanlara çevre bilincini ve manzara resmini sanatı aracılığıyla tanıtmaya çalışmıştır. Çalışmaları 19. yüzyıl Amerikası’nda yaşanan hızlı teknolojik gelişmelere bağlı olarak insanlığın adeta eskiyi kaybederek ve kendi öz değerlerinden uzaklaştığına vurgu yapar gibidir. Ressamlığının yanı sıra yazar ve şair olarak da pek çok çalışmaya imza atmıştır. Amerikalılara bir İngiliz olarak sahip oldukları vahşi güzellikleri ve resim sanatlarını önemsemeyi hatırlatan bir yabancı ressamdır.
Thomas Cole and His Art
anemon
Keywords: Painting; American Painting; Hudson River School Painters; 19th Century; Landscape; Resim; Amerikan Resim Sanatı; Hudson River School Ressamları; 19.Yüzyıl; Manzara